2017
DOI: 10.1136/jech-2016-208730
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and health outcomes in an economically deprived population: the Liverpool Lung Project

Abstract: Smokers from deprived backgrounds in Liverpool showed increased risk of developing pneumonia, emphysema, chronic obstructive pulmonary disease, bronchitis, lung cancer, other types of cancer, cardiovascular disease and diabetes. These findings are in line with the literature and may help to inform public health policies and ultimately work towards addressing smoking-related health inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…The findings from this analysis are aligned with the limited available literature. Specifically, we found that patients with cancer who were smokers were younger and more commonly males compared with patients with cancer who were not smokers, which is in line with the literature 10 32. Additionally, smokers had, on average, almost 20% higher total monthly healthcare costs than non-smokers.…”
Section: Discussionsupporting
confidence: 89%
“…The findings from this analysis are aligned with the limited available literature. Specifically, we found that patients with cancer who were smokers were younger and more commonly males compared with patients with cancer who were not smokers, which is in line with the literature 10 32. Additionally, smokers had, on average, almost 20% higher total monthly healthcare costs than non-smokers.…”
Section: Discussionsupporting
confidence: 89%
“…Smoking and excessive alcohol consumption lead to increased health risks, these lifestyle habits must therefore become targets for interventions to reduce the global CAP burden. 35 36 In addition, more effective strategies are needed to improve vaccination coverage since less than one-third of the population at risk in our study had received influenza and/or pneumococcal vaccines even though these are recommended by local scientific societies. Both vaccines are available free of charge in General Roca, and influenza vaccine is available free in Rivera.…”
Section: Discussionmentioning
confidence: 96%
“…Health behaviors are important to understanding population health disparities as they are empirically linked to multiple health outcomes and can ultimately lead to increased health care costs and premature death. For example, smoking is associated with a number adverse health outcomes including acute myeloid leukemia and cancers of the stomach, liver, bladder, cervix, pancreas, kidney, and esophagus ( Helms et al, 2017 , Sherratt et al, 2017 , HHS, 2014 ). Stroke, cataracts, coronary heart disease, chronic obstructive pulmonary disease, pneumonia, emphysema, bronchitis, lung cancer, diabetes, cardiovascular disease, immune function issues, and overall diminished health are also more common among smokers (HHS, 2014, Sherratt et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, smoking is associated with a number adverse health outcomes including acute myeloid leukemia and cancers of the stomach, liver, bladder, cervix, pancreas, kidney, and esophagus ( Helms et al, 2017 , Sherratt et al, 2017 , HHS, 2014 ). Stroke, cataracts, coronary heart disease, chronic obstructive pulmonary disease, pneumonia, emphysema, bronchitis, lung cancer, diabetes, cardiovascular disease, immune function issues, and overall diminished health are also more common among smokers (HHS, 2014, Sherratt et al 2017 ). Physical inactivity is associated with chronic diseases such as cardiovascular disease, diabetes, asthma, arthritis, cancer, and hypertension as well as premature death ( Warburton et al, 2006 , Humphreys et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%